2013
DOI: 10.1111/bij.12109
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of willow grouse (Lagopus lagopus) in the Arctic: taxonomic discordance as inferred from molecular data

Abstract: Using independently segregating nuclear single nucleotide polymorphisms (SNPs) and mitochondrial control region sequences, we found an east–west division among sampled willow grouse Lagopus lagopus subspecies. This division cut across the range of the subspecies with the largest distribution (lagopus) and thus contradicted existing taxonomic classifications. Russian Lagopus lagopus lagopus tended to cluster with North American willow grouse partly classified as other subspecies. Scandinavian willow grouse (L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Contradicting taxonomic classification in subspecies level of another Tetraoninae species was revealed in willow grouse ( Lagopus sp.) (Höglund et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Contradicting taxonomic classification in subspecies level of another Tetraoninae species was revealed in willow grouse ( Lagopus sp.) (Höglund et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological analyses of fossil remains of the two sister species have shown that both were morphologically distinct and probably had greater body weights than their modern counterparts (Bochenski, ; Potapova, ; Stewart, ). However, it has not yet been established whether these populations represented specialized lineages that went extinct during end‐Pleistocene climate warming, approximately 10 thousand years ago, or if the glacial populations in fact are the direct ancestors of modern European L. lagopus and L. muta (Höglund et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the red grouse subspecies shows an identical pattern to the Norwegian sample, thus corroborating the shared history between the British red grouse and Scandinavian willow grouse (Höglund et al., 2013). We were also able to show that following the LIG, the method does indeed capture lineage‐specific population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This is seen in the divergent population size trajectories of willow grouse samples originating in Scandinavia and Britain versus Siberia and Alaska. This result further validates the observed genetic substructuring within the L. lagopus lagopus clade, where the Russian individuals cluster closer to the North American willow grouse ( L. lagopus muriei and L. lagopus alexandrae ) than to the Scandinavian willow grouse (Höglund et al., 2013). In fact, the overall similarity between the Siberian and Alaskan trajectories with the major exception being the much larger bottleneck in the Alaskan sample points to the recolonization of Alaska by the Siberian individuals during the last ice age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation